Relevansi Pemikiran Ekonomi Ibnu Taimiyah Abad ke-13 M terhadap Pengembangan Ekonomi Islam Kontemporer - rezki ananda putra; Kamiruddin amin; Ahmad Abdul Mutalib (Universitas Persada Indonesia YAI, 2025)
This study aims to analyze the relevance of Ibn Taymiyyah’s 13th-century economic thought to the development of contemporary Islamic economics, focusing on the concepts of fair price, market mechanisms, anti-monopoly principles, and the role of the state in maintaining economic balance. This research employs a qualitative approach through library research by examining Ibn Taymiyyah’s primary works as well as secondary literature consisting of books and scholarly articles discussing his economic ideas. The findings reveal that the concepts of al-tsa’man al-mithli (fair price), honesty in trade, the prohibition of hoarding and market exploitation, and the role of the state through the hisbah institution align closely with modern economic theories and remain highly relevant to contemporary economic challenges. These principles can be applied to analyze issues such as oligopolistic market structures, price fluctuations in essential goods, digital trade regulation, and consumer protection in technology-based economies. This study concludes that Ibn Taymiyyah’s economic thought is not merely of historical significance but also provides strong normative and analytical foundations for the advancement of modern Islamic economics that uphold justice, public welfare, and the principles of Sharia.